(untitled) (Third Sector Social Economic Review, 2023)
In this study, fund returns are classified as successful/failed according to the fund’s benchmark/theresold value returns. In terms of performance measurement, mutual funds are subject to the “Communiqué on Principles of Performance Presentation and Performance-Based Remuneration for Individual Portfolios and Collective Invesment Schemes, and of Grading and Ranking Activities of Collective Investment Schemes (VII-128.5). The fund returns are categorized in this way in accordance with this Communiqué, taking into account that a ""Benchmark"" is chosen in accordance with the investment strategy of the portfolio that the funds will manage in order to compare the return of the portfolio and the characteristics of the assets and transactions invested in, and the threshold value is used to compare the returns of the portfolios without benchmarks. Examining the elements that affect the success of mutual funds is the primary driver of this study. A number of variables have been looked at for this purpose, including the fund’s management fee rate, the number of investors, the number of portfolio managers managing the fund, the equity capital of the portfolio management company managing the fund, the size of the portfolio it manages, whether the portfolio management company managing the fund is a subsidiary of the bank, the amount of time it has been in the industry, and the fund’s 6-month return. The influences on the success of mutual funds were examined and interpreted using the logistic regression approach in accordance with the study’s objectives. The study’s primary conclusions state that the number of portfolio managers overseeing the fund and the fund’s six-month return are two of the key elements influencing mutual funds’ success.